Investigation of the Physical Properties and Droplet Combustion Analysis of Biofuel from Mixed Vegetable Oil and Clove Oil - Adhes Gamayel; Mohamad Zaenudin; M. N. Mohammed; Eddy Yusuf (Science and Technology Indonesia, 2022)
The study of vegetable oil used as fuel in conventional engines leads to problems like the low volatility and high viscosity. This research aims to evaluate the droplet combustion characteristics that correlated with the density, viscosity, and the flash point of the biofuel from mixed vegetable oil with clove oil. Biofuels used in research are Jatropha Oil (CJO), Kapok Oil (KSO), Coconut oil (CCO), and all biofuel mixed with clove oil in 5% basis volume. Fuel properties that tested both biofuel and fuel mixture using the ASTM method are density (ASTM D1298), viscosity (ASTM D445), The flash point (ASTM D93). The droplet combustion experiment used suspended droplets placed in the junction of the K-type thermocouple and the Ni-Cr wire (as the coil heater) to heat the droplet until the combustion occurred. The result indicates that adding 5% clove oil in biofuel creates higher density, the viscosity decreases until 10%, and the flash point decrease to 30%. Droplet combustion results that adding 5% clove oil creating a more complete combustion process in CCO than KSO and CJO. Higher viscosity in KSO and CJO leads to eugenol and terpene (clove oil compound) trapping in the fuel droplet. Due to eugenol and terpene having great volatility, they are evaporating rapidly leading to secondary atomization and micro-explosion phenomena.